Esettanulmány alapú online kollaboratív tudásépítés vizsgálata: A tudásépítő interakciók kapcsolatrendszere az elégedettséggel és az eredményességgel - Dorner, Helga; Konyha, Rita (Magyar Pedagógia, 2015)
This study focuses on the relationships between online interactions, perceived satisfaction and group performance within small groups, whose members collaborated in a problem-based learning scenario. Werelied on the Community of Inquiry model (Garrison, Anderson,& Archer, 2000) to explore the social, cognitive and instructional dimensions of the small-group collaborations; Wealso investigated how these dimensions relate to participant satisfaction and perceived group performance. Transcripts of interactions among the group members and their facilitators were analysed by two independent coders using content analysis. Satisfaction with the process and group performance were surveyed post hoc. Results revealed a strong correlation between process satisfaction and interactions characterized by manifestations of social presence. Teaching presence was linked to satisfaction with thefacilitator and the process. Performance satisfaction correlated with cognitive presence and with interactions aimed at exploration and analysis, in particular. The current study did not find any relationship between perceived group performance and collaborative interactions, thus requiring further exploration. Wealso discuss the limitations of the study.